Persecuzione e diaspora dei musicisti ebrei durante le leggi antisemite (De Musica, 2023)
In this essay, I illustrate how the fascist regime was related with the Jews, especially the Jewish musicians (e.g., Mario Castelnuovo-Tedesco), and how the Jewish musicians dealt with the fascist dictatorship in the early years until the advent of anti-Semitic laws, as they upset the world of music and musicians, with a reference to the actions of Arturo Toscanini.